Methanesulphonic acid in aerosols along a cruise path from China to the Arctic Ocean: Spatial and temporal distributions and link with iodine - Haoran, Liu; Zhouqing, Xie; Peipei, Ye; Hui, Kang; Siqi, Xu (Polar Research Institute of China - PRIC, 2015)
Methanesulphonic acid (MSA) may play an important role in the climate change occurring in response to the warming of the Arctic Ocean. However, the spatial and temporal distributions of MSA in this region are poorly understood. We report on the MSA content of aerosols over oceans measured during the 3rd Chinese National Arctic Research Expedition (CHINARE2008) from July to September, 2008. Results show that the aerosol MSA content can be influenced by multiple processes in different areas. In coastal regions, airborne pollutants, especially nitric oxide, may strongly influence the oxidation of dimethyl sulfide (DMS) and increase the concentration of aerosol MSA. In remote areas of the Pacific and Arctic oceans, changes in plankton will indirectly influence the airborne MSA concentration. Moreover, we found fairly similar trends in the variation of the concentrations of total iodine (TI) and MSA in the Arctic during CHINARE2008, suggesting that iodine and MSA may come from similar sources in the Arctic. Compared with the findings from other two cruises, CHINARE1999 and CHINARE2012, we found that sea ice is an extremely important factor that influences the aerosol MSA content in the Arctic. In addition, MSA concentrations may increase in the Arctic in the future caused by sea ice melting due to global warming.